Informação, patrimonio e mémoria: cultura e arte barroca em Ouro Preto - Neide Nativa (2016)
This dissertation is the result of a study concerning the Specialization Course in Culture and Baroque Art (CECAB), offered by the Philosophy, Arts and Culture Institute (IFAC) of the Federal University of Ouro Preto, Brazil. The aim of the research is to analyze and apprehend the meaning behind the course, having its institutional memory as an axis, and to spot its contribution to the field of cultural heritage of Brazil in terms of professional qualification and scientific knowledge production. The theoretical contribution has been based on three fundaments the concept of the Baroque Heritage and Culture, essential for the understanding of the purpose of the research; the constitution of the Memory as a sedimentation area for the knowledge; and the purpose of the Information Science as a space for the construction and interlocution of Memory tales. The methodology related to the qualitative approach consisted on the recovery and analysis of archived documents and academic studies, by collecting information from semi-structured interviews and oral reports from faculty and from students. The development of the research led to the evidence of the CECAB's historical path, the impasses and challenges faced, the faculty and the students, the content of the courses, the production of 200 monographs and which of those have been converted into master's researches, PhD theses, published as books, and the IPHAC's magazine. The results yielded to the fact that the CECAB was a relevant and fundamental course for shaping specialists and generating knowledge regarding Baroque Art and Culture, becoming strategic and contributing to Brazilian Cultural Heritage. The research also enabled the reconstitution of part of the course's institutional memory.